Solidarity and Poland : impacts East and West / edited by Steve W. Reiquam ; with the assistance of Cathie M. Lorenz - Reiquam, Steve W.Lorenz, Cathie M.
Texto presentado en la conferencia "The legacy of Solidarity", celebrada los días 10-12 de febrero de 1987en el Woodrow Wilson International Center for Scholars, patrocinada por East European Program, the Kennan Institute for Advanced Russian Studies, y el Research Institute on International Change.